Exploring the Link Between Wages and Psychological Capital. (July 2022) - Beck, Jason
Traditional Mincer-type hedonic wage equations typically fail to account for the effect of psychological capital, in part because such factors are often regarded as unobservable. This article incorporates a measure of psychological capital (specifically, self-esteem) that has been validated in the psychology literature into an otherwise typical hedonic wage model. Then, the sample is divided into race and gender subgroups and estimates are compared. The results suggest that self-esteem does play a role in determining wages for Whites (White men, in particular), but it has no detectable effect on the wages of African-Americans. Data are drawn from the 1979 National Longitudinal Study of Youth. JEL: D ('Microeconomics'), J ('Labor and demographic economics'), J31 ('Wage levels and structure, wage differentials')